2020
DOI: 10.1186/s13014-020-1480-0
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic body radiotherapy (SBRT) for adrenal metastases of oligometastatic or oligoprogressive tumor patients

Abstract: Introduction: Local ablative treatment strategies are frequently offered to patients diagnosed with oligometastatic disease. Stereotactic body radiotherapy (SBRT), as ablative treatment option, is well established for lung and liver metastases, whereas for isolated adrenal gland metastases the level of evidence is scarce. Material and methods: This single-institution analysis of oligometastatic or oligoprogressive disease was limited to patients who received SBRT to adrenal metastasis between 2012 and 2019. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 49 publications
2
48
3
Order By: Relevance
“…Zhao 13 reported that BED≥85.5 Gy and a volume of GTV<30 cm 3 were correlated with LCR in univariate analysis. Konig et al 22 found a superior local control if BED 10 was ≥75 Gy or the volume of PTV was <100 mL, but these findings were not significant. Buergy et al 12 reported that neither lesion size nor radiation dose were significant factors for local control.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Zhao 13 reported that BED≥85.5 Gy and a volume of GTV<30 cm 3 were correlated with LCR in univariate analysis. Konig et al 22 found a superior local control if BED 10 was ≥75 Gy or the volume of PTV was <100 mL, but these findings were not significant. Buergy et al 12 reported that neither lesion size nor radiation dose were significant factors for local control.…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, BED 10 of adrenal metastases was often lower than lung or liver metastases. 3 , 23 The range of BED varied from 30 Gy 9 to 151 Gy 22 in published studies about adrenal metastasis, and the median BED ranged from 60 Gy 24 to 112.5 Gy. 14 In our study, a portion of the lesions was given lower BED to protect the adjacent vital organs; the median BED was 84 Gy, and hence consistent with other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Late toxicity occurred in only three patients. Two patients each suffered from grade I and II fatigue, and one patient had grade I gastrointestinal toxicity [30].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence of the effectiveness of Stereotactic Body Radiation Therapy (SBRT) has recently been published [1][2][3][4][5][6][7][8][9][10][11]. It has also been reported that curative treatment for oligometastasis from primary tumor in the setting of local tumor control improves disease-free recurrence time and overall survival.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that curative treatment for oligometastasis from primary tumor in the setting of local tumor control improves disease-free recurrence time and overall survival. The adrenal glands are often the site of a solitary metastasis, especially from lung cancer [3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%